Managing waiting lists at an outpatient clinic by improving the production planning process - Eriksson, Simon; Tedenbrant, Linda (My University, 2015)
Waiting lists at hospitals are becoming an increased problem in Swedish healthcare. The requirements of efficiency at healthcare clinics increase further with political pressure of providing appointments within 90 days to all patients who seek specialized care. The gynecological outpatient clinic at Skaraborg’s hospital in Skövde is one of the Swedish clinics experiencing difficulties regarding the waiting list situation. It has been shown that an improved production planning and control (PPC) process can ease the waiting list situations in terms of increasing the controllability. The gynecological outpatient clinic at Skaraborg’s hospital in Skövde has therefore requested some improvement suggestions regarding the PPC process as means to control the waiting list situation in order to enable the clinic to sustain waiting lists within target levels. The purpose of this study is to provide such improvement suggestions. The study was conducted through gathering of data about the current PPC process at the gynecological outpatient clinic, by studying a different PPC process at another outpatient clinic at Skaraborg’s hospital, and by literature studies. The current PPC process was mapped and an analysis of the current situation was conducted. The analysis revealed six main problem areas in the current PPC process. The first three problem areas found were related to poor ability to adapt lower level planning with upper level planning, to lacking of a short term planning method and to planning based on the available staff rather than the requested staff. The other three problem areas were found within supporting functions of the PPC process. One was related to poor forecasting ability, one to poor considerations of care requests when planning and one to poor waiting list prediction ability. The problem areas then acted as a basis to generate improvement suggestions. An improved PPC process was suggested in which capacity planning was suggested to be based on capacity requirements, created by patient demand. Improved forecasting in combination with better information quality of care requests was also recommended. These changes would allow the clinic to foresee the capacity requirements and the development of the waiting list and thus provide the clinic with ability to react in time and, by doing so, control the waiting list levels. The improvement suggestions were critically evaluated and further studies were suggested to support the potential implementation of the improvement suggestions.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics